An IPD framework for sustainable design in UUM campus development - Abdul Nifa, Faizatul Akmar; Mohd Nawi, Mohd Nasrun; Abdul Rahim, Syukran (2014)
The growing number of users in a university campus calls for a more sustainable approach in the design of infrastructure and facilities available on campus. To date, Universiti Utara Malaysia (UUM) has approximately 25,000 users on campus which includes students and staff. With the second largest international student population among Malaysian universities, it is imperative that the campus development to be at par with international universities especially in the matters of sustainability. This paper reports part of an on-going research for developing a framework for JPP UUM which strengthens the efforts of sustainability in the development of UUM campus. Through a number of pilot interviews, a framework for integrated project delivery is derived from themes identified in the insights of various functions within JPP UUM. It is concluded that a more proactive approach from the campus management is needed to ensure all components in the framework to come together for sustainable efforts to succeed.